Robotic Rehabilitation and Transcranial Direct Current Stimulation in Children With Bilateral Cerebral Palsy - Raess, Liliane; Hawe, Rachel L.; Metzler, Megan; Zewdie, Ephrem; Condliffe, Elizabeth; Dukelow, Sean P.; Kirton, Adam (Frontiers in Rehabilitation Sciences, 2022)
AIM: To identify challenges of combining robotic upper extremity rehabilitation with tDCS in children with upper extremity bilateral cerebral palsy (CP) by assessing feasibility, tolerability and safety. METHODS: This was an unblinded, open-label, pilot clinical trial. Participants completed 10x1 hour sessions of robotic rehabilitation combined with motor cortex anodal tDCS. Feasibility, acceptability and practicality, were assessed including the number of participants completing the protocol, factors limiting participation, time required for sessions, and completion of functional assessments and tolerability scales. To assess safety, standardized clinical and robotic measures of sensorimotor function were performed. The trial was registered at clinicaltrials.gov (NCT04233710). RESULTS: Eight children were recruited (mean age 8y±1.8y, range 6-11 years) and 5 completed the intervention. There were no serious adverse events. One child developed focal seizures 6 weeks after the trial that were deemed to be unrelated. Barriers to completion included time and scheduling demands and patient factors, specifically cognitive/behavioural impairments and dyskinesia. No decline in clinical function was appreciated. CONCLUSIONS: Robotic upper extremity rehabilitation combined with tDCS may be feasible in children with bilateral CP. Careful participant selection, family engagement, and protocol adaptations are recommended to better understand the feasibility and tolerability of future trials.